청각장애 대학생의 경험에 기초한 독해력 및 문장력 향상을 위한 교수-학습 전략 탐색 - 권순우(Soon-Woo Kwon) (언어치료연구, 2005)
본 연구는 현재 C, D, N대학교에 재학 중인 3명의 청각장애 학생이 학교 교육을 받아오면서 현재의 독해력 및 문장력을 갖출 수 있도록 도움을 준 여러 가지 학습 방법을 알아보고, 분석하여 이를 근거로 하여 청각장애 학생의 언어지도를 위한 방향을 재정립하여 그들의 독해력 및 문장력 향상에 도움을 줄 수 있는 기초적인 자료를 제공하고자 하였다. 이 연구를 통해 얻어진 청각장애 학생의 교수-학습 전략을 제시하면, 첫째, 학습 방법을 총체적으로 접근하고, 이를 유기적으로 조직화 하여야 한다. 둘째, 청각장애 학생에 맞는 다양한 읽기 지도 프로그램의 개발이 시급하다. 셋째, 교육과정 운영에 있어서 학교 사정에 따라 통합 주제로의 전환이 필요하다. 넷째, 문제 해결을 위한 다양한 매체 자료를 활용하여 다 매체적 접근이 이루어져야 한다. 다섯째, 청각장애 학생을 위한 다양한 언어지도 교육의 필요성이 강조되어야 한다. The purpose of this study is to offer basic data which benefit students with hearing impairment to elevate ability to read and understand, and ability to compose, by rethinking direction for their language instruction through finding out various learning methods which helped them acquire present comprehension and composition, and analyzing it. The subject was selected 3 students with hearing impairment who attend C., D., N., university. The teaching and learning strategies for improving their comprehension and composition drawn from this study are as follows; First, it should be focus learning methods upon a system organically such as making it holistic approaches. Second, it should be developed various reading instruction program fitting to them. Third, in curriculum management, it should be shift curriculum management to inclusive theme under the school circumstance. Fourth, it should be done multi-media approach applying various media materials for problems solving. Fifth, it should be stressed necessity of various language instruction for students with hearing impairment. KCI Citation Count: 15